The motives, pattern and form of Anglo-Ottoman diplomatic relations, c. 1580-1661 - Saunders, L; Liane Saunders (1994)
﻿ My study covers the period from the initial establishment of English representation at the Ottoman Porte with the capitulations of 1580 which established trading and diplomatic rights for English merchants, and the formal establishment of an embassy in 1583. I explore the development of the English embassy at Constantinople from its vulnerable first years through its growth in prestige during the 1620s and 1630s, to the zenith of its influence in the 1660s before the French began to dominate diplomatic business at the Porte. I examine English policy at the Porte from its first tentative attempts to secure a strategic alliance against the Spanish with the Ottomans in the Mediterranean, through the Thirty Years War in which both Ottoman and English authorities found themselves reluctantly embroiled and the domestic troubles which both suffered in the 1640s, culminating with the execution of Ibrahim I in 1648 and Charles I in 1649. I conclude with the period of stabilization in the 1650s when the English authorities reasserted coherent policies at home and abroad during the Protectorate and the Restoration. This was mirrored by a stabilisation of the Ottoman Empire after the first of the Köprülü Grand Viziers took the reins of power in 1656 and reasserted central control over the provinces and over Ottoman vassals on the peripheries of Ottoman territory. The thesis builds on work done on the English commercial expansion in the Levant and the commercial role of the embassy in the Constantinople. I seek to complement existing studies of particular embassies and personalities and to give a broader over-view of the development of Anglo-Ottoman diplomatic relations. I intend to open debate on the development of Ottoman foreign policy and the implementation of Ottoman diplomacy during the seventeenth century well before the Ottoman bureaucracy underwent the westernization which led to it being absorbed into the European diplomatic system during the late eighteenth century. In the introductory chapters I explore the development of diplomacy during this period to establish the different attitudes of the English governments who conducted a largely adhoc diplomacy until the late sixteenth century when they began to open a few key residences abroad, and the Ottoman authorities who maintained a strictly non-reciprocal form of policy with western nations which lay outside the Dar al-Islam or Muslim lands. I discuss the question of the duality of the embassy at Constantinople as both a commercial agency and a state department and examine the potential for conflict between the controlling interests of the Crown and the Levant Company. In two chapters on the domestic situations in England and the Ottoman Empire I assess the priorities of policy and the domestic and financial constraints on an active foreign policy. Both the Ottoman Empire and the English sought to secure their own state through internal stability and external alliances. Both states faced the same problems of hostility from their neighbours, internal rebellion and the need to provide for growing government expenditure. However, England and the Ottoman Empire differed in the way they approached their problems and had different resources to help them carry their policies through. The most notable contrast was that the Ottomans possessed a growing standing army while England relied on ad hoc levies until Cromwell's new model army. These chapters are intended to open the subject to two audiences: the Ottomanist and the Early Modern European/English Historian, and to place the Anglo-Ottoman relationship within a broader diplomatic context. I have divided the thesis into three parts, each exploring a different aspect of diplomatic relations between Whitehall and the Porte, centring on the role of the embassy at Constantinople. The opening of direct diplomatic relations with the Porte was the first sustained diplomatic contact the English had established with a non-Christian nation and formed the model for later diplomatic contacts with non-European nations. As a whole, my study contributes to an understanding of how England adapted to the non-reciprocal diplomacy of the Ottoman Porte and to the operation of diplomacy by a Christian nation in a non-Christian state. I also explore the development of English policy in the Mediterranean and place the Anglo-Ottoman diplomatic relationship in its European context. In part one I examine the function of the etiquette system at the Ottoman Porte and assess the importance of protocol conventions and the extent to which they affected the status of the ambassador and the progress of negotiations. I explore the status of western ambassadors within the Ottoman system and illustrate the adaptability and sophistication of the Forte's ceremonial system. I address the problem of the Forte's attitude to western states, recognising that there was ambiguity over whether such states were treated as representatives of tributary states or as honoured guests. I also explore the role which gift-giving, both official and unofficial, played in assessments of status and the complicated issue of diplomatic precedent, where western ambassadors attempted to assert their own concepts of status on the Ottoman system. In a further chapter I demonstrate how the English ambassador fitted into the English Court system and contrast English diplomatic ceremonial with that of the Porte. I provide an outline of the development of the conflict between the Crown, which endorsed the ambassador, and the Levant Company, which paid for him, to resolve the question of whether the embassy in Constantinople was indeed an embassy in the true sense. In this chapter I also explore the position of the few quasi-official Ottoman representatives who attended the English Court despite the official non-reciprocal diplomatic stance of the Porte. I examine the ceremonial which was provided for them and illustrate how the English system adapted to deal with this new phenomenon. This first part does not stand in isolation from the sections dealing with actual negotiations at the Porte but I intend it to place the diplomatic representatives in the framework in which they operated and establish the principles of status through which they proceeded to negotiations. In part two I consider the development of the administrative structure of the embassy in Constantinople. I include an assessment of both English and local staff, and attempt to resolve questions of the experience and efficiency of administrative personnel and of the ambassadors whom they served. I also explore the function of the embassy and establish the chains of command and channels of communication which the embassy involves. I explore the development of chancery practice during this period and give an outline of the Ottoman petition system through which all negotiations were initiated. I confront the problem of prompt authorization of documents and examine the use of a possible 'deputed Great Seal' by the embassy. The roles of Ottoman officials, especially the role of the Grand Vizier and the developing role of the Reisūlkūttab (Chief Scribe to the Divan) in foreign affairs are also discussed. Finally, in this section I consider the problems of security and communications within the region and examines the importance of the English consular network. The purpose of this section is to build up a picture of the operation of the embassy on a day to day basis to from a background to the various negotiations discussed in the final section. The final section forms the bulk of the thesis where I assess policy development in Anglo-Ottoman diplomatic relations. In the chapters of this section I explore the various types of negotiations conducted at the Porte by English ambassadors. Because the greater weight of accessible evidence is that of the English sources, the structure of the chapters is determined by English considerations and interests in the region. Nevertheless, I have made some attempt to balance this with Ottoman sources where possible. In the first chapter in this section I deal with the nature of the capitulations, the grants of privileged status, by which the English communities were permitted to live and trade in the Ottoman Empire. I discuss the different interpretations placed upon these capitulations by the Porte, which viewed it as a unilateral grant given personally by the sultan, and by western ambassadors, who viewed it more as a bilateral agreement. I explore the ways in which the ambassador regulated the merchants and registered their contracts to provide legal protection for their commercial activities. I examine the advantages of the English Company structure over the more disconnected consular and commercial structures which the French and Venetian communities used. The English system simplified the chain of command from the English ambassador to the English merchant community and ensured that changes in commercial practice required to protect the merchants could be implemented rapidly. This made the English the most successful trading nation in the region. The Dutch, who did not gain independent status at the Porte until 1612 tried to emulate the English custom of using an officer of dual diplomatic and commercial status. They did so with some success in the early years of their residence at the Porte but failed to establish the embassy support team upon which the English used to such effect. This meant that Dutch success was completely dependent on the calibre of their agent which diminished from the late 1630s. In this chapter I also explore the cooperation and competition between the resident western ambassadors to gain extra status and privileges for their communities. In a further chapter I examine the different experiences of the English communities in Constantinople, Smyrna and Aleppo, and highlight the problems which English merchants encountered with local interpretations of and indifference to the Capitulations, thus contributing to the debate on the extent of central Ottoman control on the peripheries. I demonstrate that the English system of locally based consuls allowed minor disputes to be settled at a local level, with only major disputes involving infringements of English diplomatic privileges referred to the ambassador and presented to the Porte as the final court of appeal. Moving out from the immediate protection of the merchant communities, I explore the development of policy in the Mediterranean zone in two chapters. The first examines the issues of security and the strategic importance of the area as demonstrated by the extension of English capitulations to cover the Barbary states and naval responses to piracy in the region. I suggest that the attitude of the English authorities towards the Mediterranean changed with the establishment of permanent, growing English communities throughout the region. The state accepted more responsibility for security in the region although it was not always suitably organised or financially able to carry its responsibilities through. The second concentrates on diplomatic attempts to deal with individual cases of piracy and the problems which that brought to ambassadors. I demonstrate the weakness of the Porte to resolve cases involving the Barbary pirates but show that where possible, the Porte was willing to do what it could to resolve genuine cases of piracy, recognising that the English authorities lacked control over all English pirates and did what they could, when they could. In this chapter I also tackle the more complicated issue of English piracy in the region and establishes the pattern of diplomacy used to free even guilty parties from Ottoman captivity. I also explore the difficult position in which the English found themselves during the Venetian-Ottoman Cretan War from 1645-69 when they were coerced to participate and accused of collaboration with the enemy by both sides. Ambassadors had to protect merchants from Venetian blockades and Ottoman conscription and did so with some success. In the final chapters I look further afield to England's wider high-level diplomatic negotiations at the Porte. In one chapter I explore the pivotal role which the Anglo-Ottoman relationship played in English hopes of containing the Habsburg threat. This encompasses the anti-Spanish alliance which first sealed Anglo-Ottoman diplomatic relations and Anglo- Ottoman participation in the balance of power struggle for the central European princedoms. I focus on the intense diplomacy of the late 1620s when the English Crown used several avenues, including the Ottoman vassal state of Transylvania, to pursue its policy of containing the Habsburgs. While more work is required on the Ottoman and Transylvanian attitudes to this policy, my examination of the English role in trying to draw the Transylvanians from an Ottoman orbit to a Protestant alliance adds a new dimension to work done on England's European foreign policy objectives. In the final chapter I assess the English commitment to a idea of a 'corps of Christendom' and the effects this concept had upon English policy at the Porte. Historians have already established that English writers and commentators in the late sixteenth and early seventeenth century clung to the notion of a united Christian community in spite of the conflicts of the Reformation. This chapter explores the manifestations of this idea at the Porte through the English mediation on behalf of the Poles in the 1620s and a joint Swedish- Transylvanian deputation in the 1650s. As part of such attempts to create a role for the English as champions of Christendom generally, the English ambassadors were also charged with the task of defending the Orthodox Church against the influence of the Jesuits and with creating an anti-Rome alliance. In these chapters I demonstrate that despite the remarkable success of the English at the Porte, there were limitations to their policy at the Porte. I emphasise that the Porte had its own foreign policy agenda, which did not dance to the tune of Western ambassadors at the Porte. I also suggest that the Anglo-Ottoman relationship should be explored as part of a wider picture as the English authorities viewed the it within a European context and saw it as a balancing element in European power struggles. My study by no means exhausts the subject of Anglo-Ottoman diplomatic relations during this period and in some ways raises more questions than it answers, begging questions about the extent of English involvement in piracy in the Mediterranean and in the Venetian- Ottoman Cretan war as well as questions about the attitude of the Porte to English involvement in Transylvanian affairs during the Thirty Years War and beyond. Nevertheless, it establishes the advantages which the English had over their rivals at the Porte and the success they achieved in their routine diplomacy at the Porte. The English were able to capitalise on their effective organisation and able ambassadors to achieve a more than adequate level of protection for English communities, trade and interests within the Ottoman Empire. They even used the Anglo-Ottoman relationship to achieve several, albeit limited, successes in establishing security in the Mediterranean and in contributing towards a balance of power diplomacy in Europe as a whole.